2015
DOI: 10.1115/1.4031899
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Analysis of Stress Corrosion Crack Growth and Related Structural Reliability Considerations

Abstract: The predetection evolution of stress corrosion cracking has been examined as a necessary preliminary to effective detection of such cracks. Anodic dissolution (AD) and hydrogen embrittlement (HE) have been considered to calculate the stress corrosion crack (SCC) growth in AA7050-T6 for a surface-breaking crack with blunt tip in an aqueous environment. Since these processes are not completely deterministic, several advanced statistical methods have been used to introduce probabilistic considerations. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Lee and Achenbach [55] analyzed the reliability of a jet engine compressor rotor blade with a fatigue crack by using DBNs; the structure of the DBNs was based on a fatigue crack growth model, and the parameters in the model were represented by the nodes. In [56], a similar method was used for the structural reliability analysis of stress corrosion crack growth. Straub [57] established a generic stochastic structural reliability analysis model for deterioration processes by using DBNs; the nodes represented the parameters in structural models, such as the fatigue crack growth model, and the structure of DBNs was constructed artificially.…”
Section: B Structural Reliability Evaluation With Bnsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lee and Achenbach [55] analyzed the reliability of a jet engine compressor rotor blade with a fatigue crack by using DBNs; the structure of the DBNs was based on a fatigue crack growth model, and the parameters in the model were represented by the nodes. In [56], a similar method was used for the structural reliability analysis of stress corrosion crack growth. Straub [57] established a generic stochastic structural reliability analysis model for deterioration processes by using DBNs; the nodes represented the parameters in structural models, such as the fatigue crack growth model, and the structure of DBNs was constructed artificially.…”
Section: B Structural Reliability Evaluation With Bnsmentioning
confidence: 99%
“…For example, Lee and Achenbach [55] calibrated the parameters of DBNs for the reliability analysis of the rotor blade of a jet engine compressor by using an expectation maximization algorithm for the incomplete available inspection data. A similar method was used in [56] for the structural reliability analysis of stress corrosion crack growth.…”
Section: B Structural Reliability Evaluation With Bnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing the probability for success/failure from probability plots leads to the risk assessment using few data and helps the cost‐effective decision‐making process. Moreover, the probabilistic distribution has been used in Lee et al 13 to introduce stress corrosion cracking growth analysis. It has been shown that unlike the deterministic methods, which give a single measure per time unit, the probabilistic ones give the distribution of the predicted crack length through the outputs based on the variability of input variables, models, and measurements and get to the reliability afterwards.…”
Section: Introductionmentioning
confidence: 99%